Non-destructive evaluation of reinforced concrete structures - Maierhofer, Christiane; Reinhardt, Hans-Wolf; Dobmann, Gerd (CRC Press ; Woodhead, 2010)
Annotation This authoritative book provides a comprehensive review of the highly important subject of non-destructive evaluation of reinforced concrete structures. Many concrete structures and elements of concrete infrastructure (roads, bridges etc) have exceeded their original design lives and are deteriorating to an extent where they are becoming dangerous. The deterioration can be internal or not obvious and therefore only shows up with detailed testing. Non-destructive evaluation of reinforced concrete structures, volume 1: deterioration processes and standard test methods gives an overview of the deterioration of reinforced concrete and testing problems, followed by a review of classic and standard testing methods.
Keywords: Reinforced concrete construction -- Deterioration.; Reinforced concrete construction -- Nondestructive testing.; elektronické knihy; electronic books